2014
DOI: 10.1161/hypertensionaha.114.03780
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Benefit Analysis of Home Blood Pressure Monitoring in Hypertension Diagnosis and Treatment

Abstract: Home blood pressure (BP) monitoring has been shown to be more effective than clinic BP monitoring for diagnosing and treating hypertension. However, reimbursement of home BP monitoring is uncommon in the United States because of a lack of evidence that it is cost beneficial for insurers. We develop a decision-analytic model, which we use to conduct a cost–benefit analysis from the perspective of the insurer. Model inputs are derived from the 2008 to 2011 claims data of a private health insurer in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…Our findings point to the low use of both ABPM and HBPM, both of which may be cost-beneficial in diagnosing hypertension from both societal 30 and payer 31 perspectives by identifying only sustained hypertension in and out of the office and by eliminating subsequent unnecessary treatment, potential adverse events from overtreatment, and unnecessary follow-up costs. The 2015 USPSTF recommendations favor ABPM over HBPM for diagnosing hypertension because of a larger number of supporting studies, 4,6 although a recent systematic review found no definitive evidence to prefer 1 over the other.…”
Section: Discussionmentioning
confidence: 89%
“…Our findings point to the low use of both ABPM and HBPM, both of which may be cost-beneficial in diagnosing hypertension from both societal 30 and payer 31 perspectives by identifying only sustained hypertension in and out of the office and by eliminating subsequent unnecessary treatment, potential adverse events from overtreatment, and unnecessary follow-up costs. The 2015 USPSTF recommendations favor ABPM over HBPM for diagnosing hypertension because of a larger number of supporting studies, 4,6 although a recent systematic review found no definitive evidence to prefer 1 over the other.…”
Section: Discussionmentioning
confidence: 89%
“…Unfortunately, providers reported a lack of resources to defray costs of home blood pressure monitors since they are not covered by many health insurance companies. Longstanding research has demonstrated cost savings and fewer physician visits [38] associated with home blood pressure monitoring, and expanding the affordability and options for out-of-clinic monitors should continue to be a health policy focus [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Depending on the insurance plan and age group categories considered, estimated net savings associated with the use of HBPM range from $33 to $166 per member in the first year and from $415 to $1364 in the long run (10 years). Return on investment ranges from $0.85 to $3.75 per dollar invested in the first year and from $7.50 to $19.34 per dollar invested [33].…”
Section: Barriers To Implementationmentioning
confidence: 99%